ANALISIS PENGARUH MEDIA INFORMASI, RELIGIUSITAS, DAN LINGKUNGAN SOSIAL TERHADAP PEMAHAMAN MASYARAKAT MENGENAI WAKAF UANG DI KECAMATAN CIBUNGBULANG, KABUPATEN BOGOR. - Ismawati, Siti Neli; Melinasari, Susi; Shiddieqy, Hasbi Ash (Sahid Business Journal : Jurnal Penelitian Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2023)
The role of cash waqf as a source of social funds is a closely related to the welfare of the people and the lack of a management system that has not been realized optimally is inversely proportional to the huge potential of cash waqf that can help improve the development of its people. This Study aims to determine the effect of information media, religiosity, and social environment on people’s understandingof cash waqf. The number of variables studied were four, consistingof three independent variables and one dependent variable. The population used in this study was the entire community of Cibungbulang District Bogor Regency, with a sample of 75 respondents using the Tabachic & Fidell method. The approach used in this study is a quantitative approach. The sampling method used probability sampling with simple random sampling technique. The data used are primary and secondary data using documentation technique and questionnaires in the form a likert scale. The analytical method used is multiple linear regression analysis using the IBM Statistical Package for Social Sciences (SPSS) Software version 25. The results of this study indicate that the variables consisting of information media, religiosity, and social environment have a significant effect on people’s understanding of cash waqf with a value significantly 0.000 smaller than the alpha value of 0.05 or 5%. However, the more dominant religiosity and social environment variables have a positive effect on people’s understanding of cash waqf, with the regression coefficient of each religiosity variable being 0.273 and the social environment variable being 0.603. The predictive ability of the three independent variables on the dependent variable is 48.1%. While the remaining 51.9% is influenced by other variables not examined in this study.